BEARING FAILURE ANALYSIS ON VIBRATING SCREEN EXCITER BASED ON EXPLICIT LUBRICATION PARAMETER CALCULATION AND MODIFIED BEARING LIFE: AN INDUSTRIAL CASE STUDY - Sayid Bahri Sriwijaya; Mohamad Haifan; Tb. Ade Rahmatullah (Trends in Mechanical Engineering Research, 2026)
This study investigates repeated failures of a spherical roller bearing type 22330 (MTBF = 23 months) on a vibrating screen exciter at a sinter plant through tribological root cause analysis, explicit EHL film-thickness calculation, and ISO 281:2007 life estimation. Why-Why Analysis identified inadequate lubricant viscosity as the principal failure driver. An explicit Dowson–Higginson line-contact EHL calculation, cross-validated against the SKF diagram method (deviation 6–10%), showed that ISO VG 100 yields κ = 3.08 and λ = 1.7–1.9 (mixed-lubrication regime), while ISO VG 220 raises these to κ = 6.13 and λ = 2.5–3.2 (full-film EHL regime). Sensitivity analysis confirms the VG 220 classification is robust across composite roughness σ* = 0.40–0.65 μm. The gap between the actual MTBF (23 months) and the nominal L₁₀a under VG 100 (≈74 months, with equivalent load P = Fr + Y₁·Fa per the spherical-roller-bearing catalogue provisions) suggests additional limiting factors, likely particle contamination or intermittent shock loading, which warrant further investigation. Per ISO 281:2007, upgrading to VG 220 is estimated to increase L₁₀a from ≈59–89 to ≈158–237 months, with a benefit-to-cost ratio exceeding 15:1. Findings support lubricant viscosity optimization as a low-cost reliability intervention; generalization to other installations requires independent validation.